Uterine Involution and Ovarian Activity in Postpartum Holstein Dairy Cows. A Review - Mohammed Ahmed Elmetwally (Journal of Veterinary Healthcare, 2018)
Following parturition in the cow, there is a significant period of sexual quiescence of variable length. This period of reproductive quiescence was found to be longer in suckling or intensively milked animals.This acyclic period is generally considered as the postpartum anoestrous period. The postpartum period constitutes an important period in the reproductive life of dairy cows because of its enormous influence upon subsequent fertility. The entire postpartum period, puerperium, is defined as the period from parturition until the genital organs return to its normal physiological and histological condition, as in normal non-gravid state. They added that any extension of the puerperium in cows might have a detrimental effect on the reproductive performance of the individual animal. Thus, the main determinant of this period is essentially dependent on the resumption of normal ovarian cycles, the manifestation of estrus behaviour and conception following insemination.
Keywords: Post-partum